Zygophyllum album saponins prevent atherogenic effect induced by deltamethrin via attenuating arterial accumulation of native and oxidized LDL in rats - Feriani, Anouar; Tir, Meriam; Hachani, Rafik; Gómez-Caravaca, Ana María; Contreras, María del Mar; Taamalli, Amani; Talhaoui, Nassima; Segura-Carretero, Antonio; Ghazouani, Lakhdar; Mufti, Afoua; Tlili, Nizar; El Feki, Abdelfattah; et al. (Ecotoxicology and environmental safety, 2020)
The current study aimed to examine, for the first time, the relationship between exposure to deltamethrin (DLM) and atherogenic lipid profile disorders in adult Wistar rats, as well as, to verify the mechanism of the beneficial role of Zygophyllum album leaves extracts (ZALE). The experimental study was assessed using DLM (4 mg/kg b.w) either alone or co administered with ZALE (400 mg/kg b.w) orally for 90 days in rats. RP-HPLC-DAD-ESI-QTOF-MS was used to identify the bioactive metabolites present in ZALE. Plasmatic and aortic total cholesterol (TC), LDL-cholesterol (LDL-C), native LDL (LDL-apo B-100) and oxidized LDL (ox-LDL) were evaluated using auto-analyzer and a sandwich ELISA, respectively. The protein expressions of LDLR (native LDL receptor) and CD36 (Scavenger receptor class B) were evaluated in aorta or liver with a Western blot. The pathology has been confirmed with lipid stain (Oil Red O). Phytochemicals analysis revealed the presence of fifteen saponins in ZALE. Rats intoxicated with DLM revealed a signiﬁcant increase in plasmatic and aortic lipid profile (TC, LDL-C, LDL-apo B-100 and ox-LDL), as well as, the concentration of the plasmatic cytokines include TNF-α, IL-2 and IL-6, compared to control. Hepatic native LDL and aortic CD36 receptor expression were increased in DLM treated group, however aortic LDL-R does not present any modification, when compared to control. The detected disturbances in lipid parameters were supported by Oil Red O applied. Due to their antioxidant activity, the bioactive compounds in ZALE as powerful agents able to prevent the pro-atherogenic effect observed in DLM-treated animals. These metabolites modulated most of inflammatory markers, prevented accumulation of lipid and lipoprotein biomarkers, regulated the major receptor regulators of hepatic cholesterol metabolism, as well as normalize lipid distribution in liver and aorta tissue.